Clinical prognostic index for tympanoplasty (PRIT) in Pediatric patients - Sevilla DY; Rivas RR; Mendoza SM; Hernandez AM; Boronat EN; Aguirre MH; Mendoza SA (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Objetive: Pediatric myringoplasty surgical failure reported is generally attributed to different factors. The purpose of this study is to develop a clinical index based on some of these factors, which will allow surgical prognosis to be predicted.  Methods: This was a cohort study of 148 patients who underwent myringoplasty and received a 6-month follow-up during the period from January 2005 to March 2107 Variables with risk for failure (RR 95%) were introduced into a logistic regression, with those with significance being selected. The following were included for the index: otorrhea, contralateral ear status and marginal perforation (clinical significance), which were assigned values of 6, 3, and 1, respectively, with adjustments being made for age.  The PRIT > 30 or < 30 cutoff point was obtained by means of ROC.  Results: A success rate of 59.6% was reported. Otorrhea, with an OR of 11.859 (95% CI: 2.441-57.626) and an assigned value of 6, contralateral ear abnormal status, with an OR of 2.484 (1.181-5.223) and an assigned value of 3, and marginal perforation, with an OR of 2.717 (.857-8.611) and an assigned value of 1, were included in the PRIT index. Adjustment was made for age, and the cutoff point was established at > 30 (p < 0.001).  Conclusions: Construction of the index was achieved. One shortfall of the study is that only one third of patients were < 7.5 years of age, which might represent a bias. All results correspond to a 6 months follow-up period. Validation will be carried out in a subsequent study.